Use of calcined sepiolite in removing phosphate from water and returning phosphate to soil as phosphorus fertilizer - Hong, Seung Hee; Ndingwan, Akem Michael; Yoo, Soo Cheul; Lee, Chang Gu; Park, Seong Jik (Journal of Environmental Management, 2020)
We investigated the application of cheap but efficient sepiolite for the removal of phosphate and the use of phosphate-adsorbed sepiolite for rice cultivation. Sepiolite was calcined under different temperatures to improve its phosphate adsorption capacity; the sepiolite calcined at 950 °C (950-SPL) was found to have highest adsorption capacity. As the calcination temperature increased, the amount of Ca eluted from sepiolite also increased, resulting in the formation of Ca–P precipitates. Phosphate adsorption on 950-SPL reached equilibrium within 12 h. Both the Langmuir and Freudlich models were not well-fitted to the equilibrium adsorption model because phosphate at initial concentration was fully removed by 950-SPL. The maximum adsorption capacity of 950-SPL with respect to phosphate was 172.34 mg/g. The phosphate adsorption of 950-SPL was endothermic and spontaneous. Phosphate adsorption at pH 3 was two times higher than at pH 11. The presence of bicarbonate significantly influenced the decrease of phosphate by 950-SPL. A breakthrough of column packed with 950-SPL/sand was not observed during >200 h. The phosphate fraction in 950-SPL was mainly composed of apatite-P and residual fraction. A toxicity test using Daphnia magna showed that the toxic units of 950-SPL corresponded to no acute toxicity. Tiller number, shoot height, shoot dry weight and total dry weight were significantly higher in P-adsorbed 950-SPL application than control. It can be concluded that calcined sepiolite can be effective in the removal of phosphate and that the sepiolite after phosphate adsorption can be used as a P fertilizer in soil.
Keywords: 950° C; Dry weight; Fertilisation; High adsorption capacity; P recovery; Phosphate adsorption; Phosphate adsorption capacity; Phosphorus fertilizer; Rice cultivation; Sepiolite; Adsorption; Fertilizers; Hydrogen-Ion Concentration; Kinetics; Magnesium Silicates; Phosphates; Phosphorus; Soil; Water; Water Pollutants, Chemical; Adsorption; Calcination; Fertilization; P recovery; Phosphorus; Sepiolite